Polymorphism and Haplotype of Mucin four gene in Iraqi women with polycystic ovarian syndrome - Faisal, Abeer A.; Almohaidi, Asmaa M. Salih (Iraqi Journal of Science, 2026)
The protein-coding gene MUC4 (Mucin 4) is positioned on chromosome 3's long arm at position q29. The current study aims to investigate MUC4 polymorphisms and haplotypes concerning polycystic ovarian syndrome (PCOS). The research involved 120 women, comprising 60 women with PCOS, and 60 healthy fertile individuals serving as a control group. This study focused on sequencing of certain segments (775 bp) from exon 11 in the MUC4 gene to identify polymorphic SNPs and haplotypes. Four SNPs in the MUC4 gene were examined. The SNP rs781407488 GG homozygous genotype showed a significant protective association with PCOS with a 0.46 odds ratio. In contrast, the GA heterozygous and AA homozygous genotypes exhibited nonsignificant risky effects with 2.02 and 3.05 odds ratios associated with PCOS.  These findings suggest that the G allele acted as a protective allele, while the A allele may be associated with the disease. The other three SNPs, rs1172519849, rs1453997681, and rs1719865600 genotypes recorded no significant differences in genotype and allele frequencies. Additionally, a high linkage disequilibrium (LD) was observed among the four SNPs of the MUC4 gene.   The genotypes GA and AA of SNP rs781407488 increased frequency act as risky factors that may associated with increasing susceptibility for PCOS in Iraqi females, while the GG genotype acts as a protective factor. The current SNPs rs1172519849, rs781407488, rs1453997681, and rs1719865600 of the MUC4 gene would inherit as one block through generation that will increase the susceptibility for PCOS and may associated with the development of PCOS.